On Unenlightened Altruism. (October 2014) - D'Souza, Jeevan F.; Adams, C. Kelly
Altruism is generally accepted to be the practice of unselfish concern for the well-being of others coupled with an associated measure of personal cost. Altruism as an actionable treatise for living aims to benefit society. While altruistic acts have traditionally been viewed as virtuous, in some cases, positive outcomes might not be forthcoming if the actor is not enlightened about the consequences of specific courses of action. While this precept has been argued extensively in historical commentary, no formal definition exists for it. This article terms this concept as 'unenlightened altruism'. The article reviews the scant extant discourse on 'unenlightened altruism' in scholarly literature, provides a formal definition for the ideology, opines consequentialist implications and correlates it to related ethical constructs. From the consequentialist standpoint, it is argued that it might be more ethical not to act than to act out of unenlightened altruism.